2013
DOI: 10.1074/jbc.m113.507426
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of Fetal Splicing Programs in Diabetic Hearts Is Mediated by Protein Kinase C Signaling

Abstract: Background: Chronic PKC activation is the leading pathogenic component of diabetes in the heart. Results: PKC␣/␤ promotes fetal splicing patterns in adult diabetic hearts via phosphorylation of the RNA-binding proteins CELF1 and Rbfox2. Conclusion: PKC␣/␤ contributes to diabetes pathogenesis by manipulating developmentally regulated alternative splicing. Significance: Identifying downstream effectors of PKC can provide novel therapeutics for cardiac pathogenesis of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
94
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(106 citation statements)
references
References 85 publications
11
94
1
Order By: Relevance
“…Finally, misregulation or misexpression of both CELF2 and RBFOX2 have been implicated as contributors to human disease including cancer, muscular dystrophies, heart failure, and Type 1 diabetes (Kuyumcu-Martinez et al 2007;Cooper et al 2009;Verma et al 2013;Nutter et al 2016). Our finding of mutual antagonism between these proteins suggests that disease-relevant splicing attributed previously to CELF2 or RBFOX2 may also be impacted by altered expression of the other.…”
Section: Implications Of Celf2/rbfox2 Antagonism For Understanding Humentioning
confidence: 55%
See 1 more Smart Citation
“…Finally, misregulation or misexpression of both CELF2 and RBFOX2 have been implicated as contributors to human disease including cancer, muscular dystrophies, heart failure, and Type 1 diabetes (Kuyumcu-Martinez et al 2007;Cooper et al 2009;Verma et al 2013;Nutter et al 2016). Our finding of mutual antagonism between these proteins suggests that disease-relevant splicing attributed previously to CELF2 or RBFOX2 may also be impacted by altered expression of the other.…”
Section: Implications Of Celf2/rbfox2 Antagonism For Understanding Humentioning
confidence: 55%
“…RBFOX2 has been shown to be dysregulated in the hearts of diabetic patients and a mouse model of Type I diabetes (T1D), where it forms a dominant negative version of the protein, leading to a number of splicing changes (Nutter et al 2016). CELF1 has also been shown to be up-regulated in diabetic hearts via PKC signaling (Kuyumcu- Martinez et al 2007;Verma et al 2013), but the global consequences of this have not been examined. By analyzing public data, we observe not only the previous finding that RBFOX2 depletion largely mirrors changes induced in a mouse model of T1D (r = 0.44) (Fig.…”
Section: Wwwgenomeorgmentioning
confidence: 99%
“…CUGBP1 has been reported to mediate alternative splicing of the insulin receptor [27] and to contribute to insulin resistance [28]. Verma et al showed that CUGBP1 is upregulated in the hearts of diabetic mice [29]. A recent genome-wide association study analysis suggested that genetic variation at the CUGBP1 locus is associated with obesity [30].…”
Section: Introductionmentioning
confidence: 99%
“…Also, we found CELF1 phosphorylation at serine 28 in malignant T cells but not in resting or activated normal T cells, indicating that the site of phosphorylation of CELF1 differs in normal and malignant T cells. PKC α/βII-dependent phosphorylation of CELF1 at serine 28 is involved in murine heart development (Verma et al 2013), but the role of phosphorylation of CELF1 at serine 28 in T cells has not been evaluated. Finding that CELF1 was phosphorylated at S28 in malignant T cells, but not in activated normal T cells suggests that different kinases that phosphorylate CELF1 at serine 28, or other positions, are expressed or activated in malignant T cells.…”
Section: Discussionmentioning
confidence: 99%